The observation of extended sources with the Hartebeesthoek radio telescope - Mountfort, Peter Ian (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1990)
The Hartebeesthoek Radio Telescope is well suited to mapping large areas of sky at 2.3 GHz because of the stability and sensitivity of the noise-adding radiometer (Nicolson, 1970) and cryogenic amplifier used at this frequency, the relatively large 20' beam of the 26 m dish antenna, and its high-speed drive capability. Telescope control programs were written for the Observatory's online computer for automated mapping. Effort centred on removing the curved baseline or 'background' from each Declination (Dec) scan, due to atmospheric and ground radiation contributions varying as the antenna is scanned. Initially these backgrounds were measured over a wide range of Hour Angle (HA) for the Dec range of a map, and an interpolated curve subtracted from each on-source scan for its HA. A common base level was established by comparison with drift scans (observed with the antenna stationary). These different observations (on- and off-source Dec scans and drift scans) were combined into one in the Skymap system by performing Dec scans at a fixed starting HA for a period long enough to permit 'cold sky' and the source to drift through. A background formed by fitting a smooth curve through the lowest sample at each Dec provides a consistent relative base level for all the scans in an observation. A high scanning speed is used so that observations may fruitfully be repeated three times and interleaved to build a reliable, fully sampled map. As each observation has its own background removed, it may be made at any HA. For comparison, maps of Upper Scorpio produced by the earlier method (Baart et al., 1980) and the Magellanic Cloud region produced by Skymap (Mountfort et al., 1987) are shown. Skymap provides a simple and flexible mapping method which relies on the stability of the noise-adding radiometer and high-speed repeated scans to produce good maps of large or small extent with little computation. Correction for drift is more difficult than with systems which use intersecting scans, such as the 'nodding' scans used by Haslam et al. (1981) or the Azimuth scans of Reich (1982).
Keywords: Radio telescopes